Mechanism of Gut-Skin Axis in Atopic Dermatitis: a Narrative Review - Susanto, Prayogi; Hardianty, Andi; Waspodo, Nurelly; Widita, Widya; Muhlis, Muhlis; Djawad, Khairuddin; Anwar, Anis (Dermatology Review/Przegląd Dermatologiczny, 2025)
Atopic dermatitis is a chronic, relapsing inflammatory dermatosis with a multifactorial etiology involving environmental, genetic, and immunological factors. Growing evidence suggests that immune dysregulation in atopic dermatitis is closely associated with alterations in the gut microbiome. Early gut microbial colonization plays a critical role in immune system development and may influence skin inflammation through bidirectional communication along the gut-skin axis. This review summarizes current evidence on the role of the gut microbiome in the pathogenesis of atopic dermatitis.